Inatismo linguístico : uma introdução ao pensamento chomskyano - Lírio Júnior, Giovani Pinto (2019)
This work intends to investigate the main aspects of Chomsky‟s linguistic innatism. To do so, our research was divided into three moments. At the first moment, we summarized the main historical and philosophical foundations that served as a basis for the rescue of linguistic innatism at the beginning of the late 20th century. Then, we did a brief description of Chomskyan innatism that sees human language as a natural object. At the second moment, we tried to understand the main concepts and methodological bases of Chomskyan innatism that culminated in the Principles and Parameters theory. Finally, at the third moment, we did a brief presentation about the main assumptions of Biolinguistics, namely: the evolution of language, the organic structure of language and the relationship between language and neuroscience.